Avaliação de diferentes técnicas de extração do glicosídio fenólico bioativo amburosídio A a partir da casa do caule de camuru (Amburana cearensis) - Lima, Marcelo Victor (2014)
Studies with extracts of vegetable origin have grown tremendously in recent years due to increased global demand for medicinal purposes. Among the raw materials used, the stem bark of A. cearensis A. Smith C has been studied because of its use to combat respiratory diseases. Compounds present in the bark, such as isocampferídio, kaempferol and amburosídio are responsible for the bronchodilator, analgesic and anti - inflammatory activity. In this context, the aim of this work is to optimize the extraction process of the present amburosídio A stem bark of A. cearensis. Initially, experiments were conducted to evaluate the effect of different processes ( Soxhlet , Maceration Dynamic and Ultrasound Assisted Extraction ) in extracting amburosídio A. Different solvents (water, ethanol and water + ethanol 1:1) were used. An experimental design was also performed to evaluate the influence of some variables (power and time) on the extraction and removal of sugars analyzed the extract by two processes: adsorption and fermentation. High Performance Liquid Chromatography coupled to Mass Spectrometry (HPLC -MS) was used to quantify the amount of the extracted amburosídio. According to the results, the extracts obtained by dynamic steeping process showed higher amounts of the compound. Extracts obtained by extraction Assisted Ultrasound showed concentration values close to that obtained by dynamic steeping. Extraction made with water + ethanol (1:1) showed greater amburosídio A content compared to other solvents. The variable power and power x time interaction were significant in Ultrasound Assisted Extraction process. Analyzing the relationship of the variables, the best condition found for amburosídio A Ultrasonic was 100% power for 6 minutes. The adsorption process was more efficient in the removal of sugar compared to the fermentation process. But both processes have reduced the concentration of amburosídio during removal of sugars.